Advances in Intelligent Tutoring Systems - Nkambou, Roger.; Nkambou, Roger.; Mizoguchi, Riichiro.; Mizoguchi, Riichiro.; Bourdeau, Jacqueline.; Bourdeau, Jacqueline. (Studies in Computational Intelligence,, 2010)
The idea for this book on Intelligent Tutoring Systems (ITS) was sparked by the success of the ITS’08 international conference. The number of presentations and their quality bore witness to the vitality and maturity of the field, and the enthusiasm of the participants held out a promise of sustainability and innovative research. Long life to ITS research! The book is divided into five parts. The introductory chapters to these parts, which summarize foundations, developments, strengths and weaknesses in each of the areas covered, are addressed to all readers. For those who want more in-depth knowledge, we give the floor to researchers who present their work, their results, and their view of what the future holds. It is our hope that all readers will find the book informative and thought-provoking.